EVALUASI KINERJA GAYA GEMPA PADA STRUKTUR GEDUNGBERTINGKAT DENGAN ANALISIS PUSHOVER BERDASAR PADA DRIFT DANDISPLACEMENT MENGGUNAKAN SOFTWARE ETABS( STUDI KASUS : HOTEL DI WILAYAH KARANGANYAR) - Nurhadi, Muhamad; Setiya Budi, Agus; Supardi, Supardi (Matriks Teknik Sipil, 2014)
Indonesia as an archipelagho the State and state wich are included in the ring of fire lanes because the path of it was meeting the Australian plate ,the Eurasian plate and the plates pasifik.Have high enaugh percentage, resulting in vulnerable regions of Indonesia earthquake shocksBased on this background,Performance Evaluation study conducted seismic forces in buildings with Pushover analysis.This study aimed todetermine the performance of the building based on the mechanism of formation of plastic hinge in the beam and column so the relationship with thebase shear displacement on the pushover curve and seismic demand curve The method used is a nonlinear static pushover analysis using ETABSprogram.Performance evaluation can be done with a nonlinear static pushover analysis which refers to the ATC - 40Based ratio value on the drift x 0,00327 and ratio values on the drift y 0,00341. So it can be safely concluded ultimit limit of performanceevaluation requirements in according with SNI SNI 03-1726 -2002.The review of velue maximum ratio of in- elastic Drift is 0,00318 and themaximum value of in- elastic ratio is 0,00332 Drift y illustrate the behavior of structures ranging from elastic conditions , in- elastic then have acondition on the verge of collapse is indicated by a decrease in the curve of the building , including the level of performance of the ImmediateOccupancy ( IO ) Based on Drift values for x and y directions is less than 0,01 then the performance of the building is included in the ImmediateOccupancy whereas in elastic drift values for x and y directions are smaller or equal with 0,005 then according to ATC - 40 level value ofperformance , including the Immediate occupancy of the results of the analysis graph building structure behaves linear pushover . The concept of strong column weak beam design is not met it is indicated the the beginning of the plastic hinge element column. When it reaches the majority of theperformance point-shaped column plastic hinge elements but the building is safe.